Carbohydrate-gel supplementation and endurance performance during intermittent high-intensity shuttle running - Patterson, S. D.; Gray, S. C. (International Journal of Sport Nutrition and Exercise Metabolism, 2007)
The aim of this study was to investigate the effects of a carbohydrate (CHO) gel on performance after prolonged intermittent high-intensity shuttle running. Seven male soccer players performed 2 exercise trials, 7 d apart. On each occasion, participants completed five 15-min periods of intermittent variable-speed running, interspersed with periods of walking (Part A), followed by an intermittent run to exhaustion (Part B). Participants consumed either a CHO gel or placebo (PLA) immediately before exercise (0.89 mL/kg body mass [BM]) and every 15 min thereafter (0.35 mL/kg BM). In addition, water was consumed at a rate of 5 mL/kg BM before and 2 mL/kg BM every 15 min during exercise. Blood glucose levels were higher (P < 0.05) at 15, 30, and 60 min of exercise and at exhaustion in CHO than in PLA. During Part B, run time to exhaustion was longer (P < 0.05) in the CHO trial (CHO 6.1 ± 1.3 min vs. PLA 4.2 ± 1.2 min). These results indicate that ingesting a CHO gel, along with water, improves performance after prolonged intermittent running in healthy male subjects, possibly by maintaining blood glucose levels during exercise.